Beneficial and Pest Arthropod Responses to Tillage and Cover Crop Residues in Organic Cucurbits. Issue 6 (30th September 2022) - Appenfeller, Logan R; Brainard, Daniel C; Hayden, Zachary D; Szendrei, Zsofia
Abstract: Reduced tillage methods such as strip tillage are often combined with cover crop mixtures to provide agronomic benefits which can support crop and soil health. However, reduced tillage and cover crop species/arrangements effects on arthropods is less understood and results of previous studies have varied. In this study, we examined how agriculturally relevant pest and beneficial arthropod species were impacted by tillage and cover crop methods in USDA-certified organic Cucurbita (L.) (Cucurbitales: Cucurbitaceae). Aphididae were the most observed foliar pests and abundance was highest in full tillage treatment plots while foliar herbivores overall, excluding Aphididae, were more abundant in strip tillage treatment plots regardless of cover crop arrangement. Formicidae was also observed more on foliage, flowers, and in pitfall traps in full tillage, similarly to Aphididae. Parasitica were the most observed foliar natural enemies with increased abundance in strip tillage treatments. Activity densities of several epigeal natural enemies were also higher in strip tillage compared to full tillage. No significant effects of tillage and cover crop treatments were observed on flower visitation rates of Eucera pruinosa (Say) (Hymenoptera: Apidae), an important pollinator of Cucurbita, while the highest visitation rates of Apis mellifera (L.) (Hymenoptera: Apidae) and Bombus spp. (Latreille) (Hymenoptera: Apidae) were in strip tillage treatments. These results suggest that reduced tillage methods can support greater abundances of natural enemies and possibly pollinators. This may lead to enhanced biological control and pollination, but impacts may vary for different arthropod species and crops.